Impact of Transanal Irrigation Device in the Management of Children With Fecal Incontinence and Constipation. Issue 3 (September 2020) - Patel, Samit; Hopson, Puanani; Bornstein, Jeffrey; Safder, Shaista
ABSTRACT: Objectives: Children with fecal incontinence and constipation can be classified into 3 groups: neurogenic bowel dysfunction (NBD) related to spinal cord defects (NBD), refractory constipation (RC), or anorectal malformations (ARMs). The transanal irrigation (TAI) device (Peristeen) was approved in 2012 by the Food and Drug Administration. This system uses a pump rather than gravity to instill water as a colonic irrigant and uses balloon occlusion of the rectum. Our aim was to evaluate the effectiveness of TAI (Peristeen) in children who failed to respond to conservative measures for stool incontinence and constipation. Methods: Retrospective study of 147 patients prescribed TAI between January 2014 and January 2020. Data collected included demographics, prior bowel regimen, symptoms before and after, patient satisfaction scores, and NBD scores. Results: Of the 147 patients initiated, 114 remain active users (13 lost to follow-up and 20 discontinued use). Multiple bowel regimens including laxatives (n = 139), cone enema (n = 40), and cecostomy (n = 7) were tried previously. The majority of our patients (n = 85) have NBD, primarily spina bifida, followed by RC (n = 43), and ARM (n = 19). For all patient groups, there was significant improvement in symptoms of fecal incontinence and constipation ( P  ⩽ 0.001). Abdominal pain was improved in the NBD and RC group, but not significantly in the ARM group. Conclusions: We provide a single-center review of a large pediatric cohort using TAI (Peristeen) for management of fecal incontinence and constipation. Peristeen offered significant improvement in patients with NBD, RC, and ARM.